Phytochemical constituents of Cadaba Trifoliata Roxb. root extract - P. Velmurugan; M. Kamaraj; D. Prema (International Journal of Phytomedicine, 2010)
Cadaba trifoliata Roxb is belongs to the family Capparaceae, important medicinal plant of Indian medicinal plants. The methanol, ethanol, ethyl acetate and aqueous extracts along with dry powder of root were screened for the presence of phytochemicals. The phytochemical constituents were analyzed by qualitative and GC-MS method. Preliminary studies showed that the presence of Tannins, Steroids, Alkaloids, Glycosides, Flavonoids and Phenolic compounds. In the GC-MS analysis, 17 bioactive phytochemical compounds were identified in the alcoholic extract. The identification of phytochemical compounds in very high peak area, 1, 2-Benzenedicarboxylic acid, diisooctyl ester (C24H38O4) with RT 24.95 has peak area 51.86% and 1-Methyl-pyrrolidine-2-carboxylic acid (C6H11NO2) with RT 6.89 has peak area 20.58%. The main important compound phytol (C20H40O) with RT 18.95 ranks with peak area 1.21%. A nature compound contains diterpene activity anti-cancer, anti-diabetic, anti-inflammatory, anti-oxidant activity and antimicrobial activity.